The Effective Management of the Islamic Education System in Indonesian Schools - H. Asep Idrus Alaw (International Journal of Educational Evaluation and Policy Analysis, 2025)
The Indonesian Islamic educational system is critical to shaping students' moral and intellectual development. Efficient administration is essential for improving educational outcomes, fostering a pleasant learning environment, and sustaining Islamic principles. As a result, the primary goal of this study is to assess the efficiency of the Islamic management system in Islamic schools by gathering information from the management teams of the selected schools. The study used a qualitative research design to collect important information from the target audience. The study's findings show the need of excellent administration in improving Islamic curricula in Indonesian educational institutions. A complete plan that blends creative teaching methods with efficient administration is required to foster a strong and vibrant learning environment. However, the results have limited generalisability to other ethnic or educational backgrounds because they are unique to Indonesia's Islamic schooling system.